Neuroinflammatory Mechanisms Involved in the Early Development and Progression of Alzheimer’s Disease - Sameena Majeed, Rifat Ullah, Mian Ayaz Ul Haq, Muhammad Zubair, Tanveer Ul Haq, Sidra Bibi (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder in which neuroinflammation has emerged as a central pathogenic mechanism. However, the temporal transition from protective to deleterious inflammation, along with its underlying mechanisms, remains poorly understood. Objective: This study aimed to systematically investigate longitudinal changes in neuroinflammatory responses and identify the critical transition window from protective to harmful inflammation in AD. Methods: A large-scale longitudinal study was conducted during July 2022 to June 2023 at the Department of Neurology, Hayatabad Medical Complex, Peshawar, Pakistan, using the 5xFAD transgenic mouse model aged 2–18 months, with quantitative assessments of glial activation states, cytokine network dynamics, inflammasome activity, signaling pathway activation, synaptic integrity, and blood–brain barrier functionality. Results: A distinct phase transition was observed between 6 and 9 months, marked by a reversal of the M1:M2 microglial polarization index from 0.67 to 1.28, alongside an increase in the TNF-α:IL-10 ratio from 0.63 to 1.75 and a 5.9-fold elevation in NLRP3 inflammasome activity. A critical threshold effect of amyloid-β42 accumulation was identified at approximately 180 pmol/g, beyond which pro-inflammatory cytokines increased exponentially while anti-inflammatory mediators declined exponentially. Hierarchical clustering revealed three major molecular modules comprising pro-inflammatory mediators, anti-inflammatory and synaptic integrity factors, and amyloid pathology, with significant negative correlations observed between the pro-inflammatory and synaptic modules. At the signaling level, chronic activation of NF-κB and p38 MAPK pathways was evident, accompanied by suppression of the AKT–mTOR pro-survival signaling pathway. Furthermore, therapeutic intervention using combined NLRP3 and TNF-α neutralization during the transition window effectively restored M1:M2 polarization balance, increased synaptic protein expression by 64%, and improved cognitive performance by 71% compared to vehicle-treated controls. Conclusion: Neuroinflammation in Alzheimer’s disease is threshold-dependent and undergoes a critical shift from a protective to a deleterious state. This transition is driven by amyloid-β accumulation, inflammasome activation, and sustained pro-inflammatory signaling. The identified transition window represents a crucial therapeutic opportunity for disease modification. Keywords: Alzheimer’s disease, neuroinflammation, microglial polarization, phase transition, NLRP3 inflammasome, cytokine network